An Investigating Students’ Perception on Asynchronous Online Language Learning during COVID-19 Pandemic: An Exploratory Study - Zakie Mahri Prasojo; Mansyur Srisudarso (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
The aims of this study are to investigate the perceptions of two vocational high school students majoring Animation and Accounting about asynchronous online learning during pandemic and how they overcome the challenges faced. This study used qualitative exploratory research design by conducting observation, interview and documentation to get rich data of the subject under focus. Moreover, the researcher used thematic analysis to analyse the data collected by following six steps proposed by Braun et al. (2019). The findings showed that asynchronous online learning strategies seemed to not fit the participants. The students more preferred learning that is conducted synchronously which for some students is perceived as a burden as they have to deal with the problem of internet data. Other findings also indicated that students who still had problem with material given were likely to have discussion with other students as an effort to overcome one of the challenges faced.